Slope Mass Rating (SMR) Classification for Rock Slope Stability and Geohazard Vulnerability Assessment - Albar, A.; Mohd-Nordin, M. M. (International Journal of Integrated Engineering, 2022)
Quantitative classification from the Slope Mass Rating (SMR) has introduced an empirical assessment for rock slope stability rating. This stability classification enables us to foresee the magnitude and susceptibility of rock mass failure towards adjacent infrastructure and human life. In this study, the stability of quarry rock slope was classified using SMR classification system and kinematic stability analysis before being correlated with geohazard vulnerability assessment. Geological formation study with site geographical survey from aerial photogrammetry technique provided comprehensive data for the study area. Fieldwork to evaluate the SMR assessment parameters was conducted by discontinuity mapping using scanline method. In-situ evaluation of rock mass such as rebound surface hardness and discontinuity characterization was carried out with rock material sampling for laboratory testing. Kinematic stability analysis presented an estimation for the direction and mode of rock slope failure. The SMR classification that constitutes geomechanics attributes had introduced the global stability rating of rock mass structure, thus facilitating the prediction of potential failure magnitude. Hence, the integration of these stability indications provides sufficient empirical estimation for geohazard vulnerability zoning for the studied area.